PENGARUH LEVERAGE DAN CASH HOLDING TERHADAP PERTUMBUHAN LABA DENGAN TAX PLANNING SEBAGAI VARIABEL MODERATING - Ulfahtun; Ajeng Wijayanti (STIE-JIC, 2021)
The underlying assumptions of this research are summarized in the following problems formulation: (1) Does leverage affect profit growth? (2) Does cash holding affect profit growth? (3) Does tax planning affect profit growth? (4) Can tax planning moderate the relationship between leverage and profit growth? (5) Can tax planning moderate the relationship between cash holding and profit growth? The aim was to determine the effect of leverage, cash holding, and tax planning on profit growth and the use of tax planning as the moderating variable for the effects of leverage and cash holding on profit growth. The samples were selected using the purposive sampling method on Property and Real Estate companies on the IDX between 2014 – 2018. The results showed leverage did not significantly affect profit growth while cash holding and tax planning had a significant effect. Moreover, tax planning was observed not to have the ability to moderate the relationship between leverage and cash holding with profit growth.